2015
DOI: 10.5603/ep.2015.0007
|View full text |Cite
|
Sign up to set email alerts
|

Przewlekła ekspozycja na hałas a niedobór testosteronu — metaanaliza i metaregresja wyników badań na gryzoniach

Abstract: Introduction: Chronic psychological distress can cause suppression of the hypothalamic-pituitary-testicular axis and thus lead to male hypogonadism, which is associated with psycho-social dysfunction, chronic diseases, and as a result, considerable economic costs. Conversely, noise is a prototypal environmental stressor of growing importance, already linked to birth outcomes and diabetes. However, its effects on male testosterone levels have been paid little attention. Material and methods: This paper reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Self-reported exposure to loud noise was also associated with lower TT, but the effect was statistically significant only among those aged ≥37 years. Our findings are in line with the relationship established in animal experiments (12), but adequate comparisons cannot be made with epidemiological studies in humans.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Self-reported exposure to loud noise was also associated with lower TT, but the effect was statistically significant only among those aged ≥37 years. Our findings are in line with the relationship established in animal experiments (12), but adequate comparisons cannot be made with epidemiological studies in humans.…”
Section: Discussionsupporting
confidence: 78%
“…Because environmental noise acts as a stressor and stimulates the HPA axis, it has been implicated as a risk factor for testosterone deficiency (10)(11)(12). There is compelling evidence from animal experiments that chronic noise exposure is associated with reduced testosterone in males: a meta-analysis (12) pooled seven laboratory studies and found that rodents exposed to about 100 dB for several weeks had more than two standard deviations lower serum testosterone than the controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Animal models have even shown that chronic noise exposure reduces male testosterone levels, which, on the other hand, might further impair their cardiovascular system. [8]…”
Section: Introductionmentioning
confidence: 99%